Coupling coordination analysis of green finance and industrial technology innovation: A case study in Zhejiang Province, China - Wang, Wenjing; Lin, Jingcheng; He, Taiyi; Zhao, Haoxiang; Zhao, Xin (Frontiers in Environmental Science, 2022)
Both of Green finance and industrial technology innovation play an irreplaceable role in the framework of sustainable development. The research on the coupling and coordination between green finance and industrial technology innovation will deepen the realization of sustainable development model. This study selects Zhejiang Province in China as the research area, uses TOPSIS entropy weight method to measure the development of green finance and industrial technology innovation in Zhejiang Province from 2012 to 2019, and uses the coupling coordination degree model to present the strength and effect of the interaction between green finance and industrial technology innovation in Zhejiang Province. The results show that: firstly, the development of green finance and industrial technology innovation in the nine cities in Zhejiang Province shows strong regional heterogeneity within the research time range. Secondly, the mutual assistance and correlation between green finance and industrial technology innovation in the nine cities of Zhejiang Province has become closer with time. Thirdly, the effect of green finance and industrial technology innovation in the nine cities of Zhejiang Province is complex. According to the research conclusion, this study puts forward policy suggestions around the role that the government, commercial banks and enterprises can perform.